Non-enzymatic covalent modifications: a new link between metabolism and epigenetics - Zheng, Qingfei (Protein Cell, 2020)
Epigenetic modifications, including those on DNA and histones, have been shown to regulate cellular metabolism by controlling expression of enzymes involved in the corresponding metabolic pathways. In turn, metabolic flux influences epigenetic regulation by affecting the biosynthetic balance of enzyme cofactors or donors for certain chromatin modifications. Recently, non-enzymatic covalent modifications (NECMs) by chemically reactive metabolites have been reported to manipulate chromatin architecture and gene transcription through multiple mechanisms. Here, we summarize these recent advances in the identification and characterization of NECMs on nucleic acids, histones, and transcription factors, providing an additional mechanistic link between metabolism and epigenetics.